Entrepreneurial Education of Russian Universities' Students as a Way to Form Agency - Morozova, Ekaterina V. (Voprosy obrazovaniâ, 2024)
The number and variety of entrepreneurship training programs in universities is growing around the world. At the same time, there is no consensus in the research field on what the future entrepreneur should be taught and how to measure the effectiveness of such training.  One of the points of view suggests that the result of teaching entrepreneurship at a university should be the formation students' "agency" - the ability to purposefully change the environment through their own entrepreneurial project.  However, at this stage, there is no agreement in the scientific and educational community on what indicators can be included in the corresponding construct, so that a reasonable conclusion can be drawn whether agency is formed in the process of entrepreneurial learning.  This article attempts to answer this question by conducting interviews with graduates of the leading entrepreneurship education programs that have been implemented both in Russian universities (formal sector, 64 interviews)) and in the informal sector of student education (24 interviews).  In this study, students' internal attitudes related to understanding the essence of entrepreneurial activity were studied, and these attitudes were compared with the theoretical construct of agency in its interpretation, presented in a series of earlier works by HSE staff (Sorokin P.S. et al.).  In the empirical part of the study, it was confirmed that the internal attitudes of students who have completed entrepreneurial training and successfully implemented their entrepreneurial project do indeed correspond to the theoretical framework of agency.  The main contribution of this article is the development of agency indicators in relation to entrepreneurial learning and the justification of their applicability for assessing the results of educational programs.